Multi-objective dynamic scheduling of serial and batch manufacturing processes - Gupta, Amit Kumar (2008)
The objective of this research is to characterize the control curves for the multi-objective dynamic scheduling (MODS) of serial and batch manufacturing processes. The pairs of conflicting objectives considered in this thesis are (1) mean cycle time and maximum tardiness, (2) mean cycle time and cycle time variance, and (3) earliness and tardiness related objectives. The motivation for using these conflicting objectives is to simultaneously incorporate the manufacturer's as well as the customer's concerns in scheduling. The interest of the decision maker lies not in just achieving a single optimal solution, but in defining a trade-off curve so that the decision maker can operate the scheduling along the trade-off curve according to the dynamic needs of the manufacturing shop.